HUBUNGAN EFIKASI DIRI DAN ISOLASI SOSIAL TERHADAP KEPATUHAN PENGOBATAN ANTIRETROVIRAL (ARV) PADA ODHA DI KECAMATAN TUREN MALANG - Kurniawan, Dedi (STIKes Maharani Malang, 2019)
Introduction: Antiretroviral therapy is the best treatment for HIV / AIDS currently. People living with hiv/aids (PLWHA) medication adherence is the most problem during ARV treatment process. Stigma is one of the main obstacles to the success of adherence to ARV therapy in PLWHA. The problem of self-efficacy and social isolation are negative emotional responses that often appeared due to stigma. Method: An analytic observational design with cross sectional approach in this study. A total of 44 people were taken by total sampling in the Turen District Health Center. Data analysis using Pearson test. Result: Pearson test results show that self-efficacy (p = 0,000; r = 0.356) and social isolation (p = 0,000; r = -0,684) have a significant relationship with ARV medication adherence. Discussion: Self-efficacy in PLWHA can reflect the confidence to be involved and adhere to treatment. Social isolation makes PLWHA avoided from the social environment and information about the disease, thus affecting treatment compliance. Social isolation has a higher correlation with antiretroviral treatment adherence compared than self-efficacy.